2021
DOI: 10.3390/nu13082509
|View full text |Cite
|
Sign up to set email alerts
|

Does Each Menstrual Cycle Elicit a Distinct Effect on Olfactory and Gustatory Perception?

Abstract: The obesity pandemic has brought forth a scientific interest in food intake and sensory perception interactions. Olfactory perception and gustatory perception are very complex and under the influence of many factors, including the menstrual cycle. This study aims to clarify conflicting findings on the influence of the menstrual cycle on olfactory and gustatory perception. Women were assessed during four consecutive phases of one complete cycle (mid-follicular, ovulatory, mid-luteal, and late luteal phases (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Such data agree with recent cross-sectional, laboratory and qualitative studies suggesting that food choices are not apparently affected by contraceptive use. 7,4145 In relation to specific taste profiles, we also observed that the present respondents reported changes in taste preferences during pre-menses (14–35%) or menses itself (15–25%), where the largest shift was in preference towards sweet foods (reported by 60% of all respondents) such as chocolate and other confectionary (reported by 25% of all respondents). Interestingly and despite consisting of a mixed contraceptive status cohort, HC participants accounted for 32% and 35% of responses for menses and 40% and 27% of responses for pre-menses across perceived taste change and food cravings, respectively, with only one respondent specifically referring to this as a withdrawal bleed.…”
Section: Discussionsupporting
confidence: 66%
“…Such data agree with recent cross-sectional, laboratory and qualitative studies suggesting that food choices are not apparently affected by contraceptive use. 7,4145 In relation to specific taste profiles, we also observed that the present respondents reported changes in taste preferences during pre-menses (14–35%) or menses itself (15–25%), where the largest shift was in preference towards sweet foods (reported by 60% of all respondents) such as chocolate and other confectionary (reported by 25% of all respondents). Interestingly and despite consisting of a mixed contraceptive status cohort, HC participants accounted for 32% and 35% of responses for menses and 40% and 27% of responses for pre-menses across perceived taste change and food cravings, respectively, with only one respondent specifically referring to this as a withdrawal bleed.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, while most of the literature has focused on sweet taste impairment in diabetes ( 4 , 10 ), we did not evaluate this taste modality. Moreover, we did not assess the possible role of other factors that may influence taste function, as well as genetic polymorphisms in taste receptor genes ( 30 ), oral microbiota ( 31 ) and hormonal fluctuation throughout the menstrual cycle ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that taste perception, food preferences, and food cravings in women are not uniform across the menstrual cycle ( Gorczyca et al, 2016 ). Food preferences and, therefore, the sense of taste and smell, are influenced by the phases of the menstrual cycle ( Stanić et al., 2021 ). However, available studies are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that the olfactory sensitivity in women using hormonal contraception was comparable to the olfactory sensitivity in women in the luteal phase of the menstrual cycle. In one study ( Stanić et al., 2021 ). women who used oral contraceptives rated higher the sweet taste of sucrose.…”
Section: Discussionmentioning
confidence: 99%